Interventions and Treatment for Nomophobia: A Systematic Review - Sujitha Jebarose Jebanesy. T; Dr.Vasantha. S (The Bioscan, 2024)
Background: Nomophobia, defined as the fear or anxiety of being without a mobile phone, has become increasingly prevalent in the digital age. This condition can significantly impact an individual's psychological well-being and daily functioning. Various interventions have been proposed to address Nomophobia, but their effectiveness remains under- researched. Objective: This review aims to systematically evaluate the existing literature on interventions and treatments for Nomophobia, assessing their effectiveness and identifying areas for future research. Methods: A comprehensive search was conducted across databases including PubMed, PsycINFO, and Scopus for studies published up to June 2024. Inclusion criteria were peer-reviewed articles that evaluated interventions for Nomophobia in adult populations. Studies were screened, and data were extracted and analyzed for intervention type, methodology, and outcomes. Results: A total of 15 studies were included in the review, encompassing psychological, behavioral, and technological interventions. Results indicate that Cognitive Behavioral Therapy (CBT) and mindfulness-based interventions showed the most promise in reducing Nomophobia symptoms. Digital detox programs also demonstrated effectiveness in specific contexts. Conclusion: While several interventions show potential in treating Nomophobia, there is a need for more rigorous, long-term studies to validate their effectiveness and to explore interventions across diverse populations.